2010
DOI: 10.1111/j.1754-9485.2010.02163.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Whole‐Breast Radiotherapy: Impact on Departmental Waiting Times and Cost

Abstract: Conventionally fractionated breast radiation therapy is delivered over 5-6 weeks. Randomised evidence has shown that hypofractionated whole-breast radiotherapy (HWBRT) over 3 weeks results in similar local control without increased toxicity. HWBRT is not standard practice in Australia for all eligible women. We examined the effect of using HWBRT (for eligible patients) on waiting lists and monetary costs. We identified factors associated with prescribing HWBRT. The Princess Alexandra Hospital Radiation Oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 18 publications
0
44
0
2
Order By: Relevance
“…Given the evidence that decreasing amount of fractions delivered decreases burden on the health care system (Dwyer et al, 2010) and the patient (Wallace et al, 1993), we believe there is sufficient evidence to suggest implementation of hypofractionation in appropriate patients will improve access to care and improve patient experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the evidence that decreasing amount of fractions delivered decreases burden on the health care system (Dwyer et al, 2010) and the patient (Wallace et al, 1993), we believe there is sufficient evidence to suggest implementation of hypofractionation in appropriate patients will improve access to care and improve patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…On an institutional level, though none of the facilities included in 2013 our analysis were from severely underserved regions, the prescription patterns for HF could reflect the providers' willingness to consider HF more often in institutions with a greater number of patients needing treatment. Previous analyses from Australia (Dwyer et al, 2010) examining the institutional cost of HF versus CF regimens, have shown that at least an extra fourteen patients could be treated each month with HF regimens and health related costs could be reduced by at least 24%.…”
Section: Discussionmentioning
confidence: 99%
“…However, HF is advantageous because it has shorter treatment time and fewer radiotherapy fractions, thereby reducing patient expenditures (28) and conserving medical resources. Thus, HF is more convenient for patients who want to seek for medical attention and improve their radiotherapy compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the less travelling intensive hypofractionated breast radiotherapy versus conventional breast radiotherapy was recently published as strongly correlated with the distance to the clinic (Page et al, 2013). Some reports reveal that an average of 20-30% of North American women forego radiotherapy after receiving lumpectomy (Chuba & Simon, 1997;Malin, Schuster, Kahn, & Brook, 2002), or choose mastectomy over breast preservation (Tuttle, Habermann, Grund, Morris, & Virnig, 2007) due to several factors, including age, psychological distress, quality of life concerns, and cost of undergoing prolonged daily radiotherapy (Dwyer, Hickey, Burmeister, & Burmeister, 2010).…”
Section: Introductionmentioning
confidence: 99%